Lipoid Proteinosis; A Case Report with Difficult Intubation - Syed Aftab Haider; Atqua Sultan; Salman Waris; Aatir Fayyaz; Zaira Salman (JLUMHS, 2018)
Lipoid proteinosis is an autosomal recessive disorder and caused by the mutations of ECM1 (extracellular matrix protein 1) gene on chromosome 1q21. It is an autosomal recessive disorder that results in deposition of hyaline material under the skin, connective tissue and mucous membranes. Hoarseness of voice occurs in infancy or early childhood. There is also thickening of the tongue and pharynx. In this case report, we present a case of 27 years old female who was presented first for emergency Lower Segment Caesarean section (LSCS) and after five months of first operation for cholecystectomy. This report is of interest for gynaecologists, anaesthesiologists and general surgeons regarding management of this rare entity patient.